Effect of liberal glucose control on critically ill patients: a systematic review and meta-analysis - Jiahui Ma; Xu Wang; Yan Zhang; Chunyan Ge (BMC Endocrine Disorders)
Abstract Background Most current guideline statements support some level of unrestricted glycemic management in critically ill adult patients. Nevertheless, the effectiveness of liberal glucose control is currently not well-supported by evidence. Therefore, our objective is to investigate the influence of liberal glucose control (> 180 mg/dl) on critically ill patients in the intensive care unit (ICU). Methods Until November 23, 2023, English language literature was thoroughly and systematically searched through multiple databases, including PubMed, Embase, Cochrane Library, and Web of Science. Our primary endpoints of interest were the occurrence of hypoglycemia, mortality in the ICU, and mortality during hospitalization. In addition, our secondary outcomes comprised of 90-day mortality, bloodstream infections, the proportion of patients necessitating renal replacement therapy (RRT), the length of time under mechanical ventilation, duration of stay in the ICU, and length of the overall hospitalization. Weighted mean difference (WMD) and relative risk (RR) were respectively computed as overall effect size for continuous and dichotomous data and reported with their 95% confidence intervals (95% CI). Results A total of 9 studies were incorporated, which included 14,878 patients in the ICU. Compared with other blood glucose target control groups, liberal glucose control significantly reduced the incidence of hypoglycemia (RR = 0.41; 95% CI:0.25 to 0.69; P = 0.001), but increased ICU mortality (RR = 1.23; 95% CI:1.03 to 1.48; P = 0.023), in-hospital mortality risk (RR = 1.18; 95% CI:1.03 to 1.35; P = 0.020), and the risk of requiring RRT (RR = 1.26; 95% CI:1.11 to1.42; P < 0.001). Conclusion Liberal glucose control can reduce the risk of hypoglycemia but increases the risks of ICU mortality, in-hospital mortality, and the requirement for RRT. To confirm the outcomes further, large-scale, high-quality clinical trials are necessary.